Social housing construction and improvements in housing outcomes for Inuit in Northern Canada. Issue 7 (31st August 2021) - Riva, Mylene; Perreault, Karine; Dufresne, Philippe; Fletcher, Christopher; Muckle, Gina; Potvin, Louise; Bailie, Ross; Baron, Marie
Abstract: One-third of Inuit households in the Canadian Arctic are in core housing need-three times the national average. In 2014–2015, over 400 social housing units were constructed in Nunavik and Nunavut, two of the four Inuit land claims regions in Canada. This article examines whether rehousing, following this large-scale construction commitment, is associated with significant improvements in housing outcomes. People on the waiting list for social housing were recruited in 12 communities in Nunavik and Nunavut. Of the 186 adults who were rehoused, 102 completed the study. Questionnaires were administered 1–6 months before and 15–18 months after rehousing. After rehousing, household crowding, major repairs needed, and thermal discomfort were significantly reduced. The sense of home, including factors such as perceived control, privacy, and identity, improved significantly post-move. Social housing construction significantly improves living conditions in Nunavik and Nunavut. Integration of housing and social policies are needed to maximize benefits of new housing construction and to avoid or mitigate unintended effects.